Rich dynamics of an SIR epidemic model - Pathak, S.; Maiti, A.; Samanta, G. P. P. (Nonlinear Analysis: Modelling and Control, 2010)
This paper aims to study an SIR epidemic model with an asymptotically homogeneous transmission function. The stability of the disease-free and the endemic equilibrium is addressed. Numerical simulations are carried out. Implications of our analytical and numerical findings are discussed critically.